(untitled) (Baghdad Science Journal, 2025)
Naidid worms were sorted from 27 samples of aquatic macrophyta including ceratophyllum demersum , Potamogeton crispus and, Hydrilla verticellat with associated filamentous algae were collected from Euphrates River at Al-Mussayab city, 60 Km southwest Baghdad. The result of sorted worms revealed the presence of eight species of subfamily Naidinae, which are consider as new records for Iraq, including Stephensoniana trivandrana; Paranais frici, Ophidonais serpentine, Specaria josinae, Dero (Dero) evelinae , Dero (Aulophorus) indicus , Nais pseudobtusa and finally N. stolci. This investigation includes morphological descriptions for each species illustrated by identification criteria photos.